Development of Arabic Pocket Dictionary for Hajj and Umrah Based on Communication Needs in Places of Worship - Amalia Fauziah Rahma; Zukhaira (LISANIA: Journal of Arabic Education and Literature, 2026)
This study aims to develop an Arabic Pocket Dictionary for Hajj and Umrah to support pilgrims’ communication during worship activities. The study used a modified 4D model consisting of the Define, Design, and Develop stages. Data were collected through questionnaires and interviews to identify pilgrims’ language needs. Based on these needs, the researchers developed an A6-sized Arabic-Indonesian pocket dictionary containing thematic vocabulary and commonly used expressions for Hajj and Umrah activities. Expert validation showed a feasibility score of 94.06%, indicating that the dictionary is highly feasible as a communication and learning resource for pilgrims. However, this study did not examine the effectiveness of the dictionary in actual communication situations.